2016
DOI: 10.1159/000449473
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Surgical Skill Transferability of the Simulator Robot to the Clinical Robot for Urology Surgery

Abstract: Introduction: Virtual reality is an increasingly popular surgical training tool in Australia, following the introduction of Australia's first virtual reality simulation machine at Liverpool Hospital, Sydney. This literature review aims at identifying gaps in previous studies, and in providing a comprehensive review of future studies to be further developed in Australia. Method: A multi-field research was performed combining the key terms ‘uro*' and ‘virtua*' and ‘simula*' and ‘robo*'. Academic search engines u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Importantly, we found that skills acquired through VR training were transferable to the inanimate environment. This finding has been previously described for prior robotic VR platforms [ 25 , 26 ] but no studies had examined transferability for the SimNow® platform. After performing VR training, residents showed major improvements in total time, total errors, and total OSATS on the inanimate drills; these improvements were demonstrated when analyzed as one cohort as well as when analyzed as individual classes.…”
Section: Discussionsupporting
confidence: 77%
“…Importantly, we found that skills acquired through VR training were transferable to the inanimate environment. This finding has been previously described for prior robotic VR platforms [ 25 , 26 ] but no studies had examined transferability for the SimNow® platform. After performing VR training, residents showed major improvements in total time, total errors, and total OSATS on the inanimate drills; these improvements were demonstrated when analyzed as one cohort as well as when analyzed as individual classes.…”
Section: Discussionsupporting
confidence: 77%
“…The use of virtual reality simulation for robotic surgery in Australia has already been described in the literature and is increasingly available in the American surgical training system. 8,9 These advances are moving so quickly that it is now augmented reality training that is being discussed as the future of surgical skill acquisition. 10 A systematic review on the use of virtual reality training for laparoscopic surgery found that operating times were significantly reduced, even when compared with training programs that included box trainer models, such as those used in the USANZ sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Training of new robotic surgeons should entail both technical and non-technical skills, including decision-making, troubleshooting, and effective communication 6 . After the acquisition of psychomotor skills and basic console orientation, the dVSS curriculum provides more complex exercises.…”
Section: Skills Maintaining Exercises and Gaining Advanced Skills In ...mentioning
confidence: 99%
“…Robotic Surgical training on a virtual simulator promises better patient outcomes with lower complication rates. Simulation allows for progress through the learning curve and is transferable to the clinical setting 6 .…”
Section: Introductionmentioning
confidence: 99%